Regulating a post-transcriptional regulator: protein phosphorylation, degradation and translational blockage in control of the trypanosome stress-response RNA-binding protein ZC3H11 - Minia, Igor; Clayton, Christine (PLoS pathogens, 2016)
The life cycle of the mammalian pathogen Trypanosoma brucei involves commuting between two markedly different environments: the homeothermic mammalian host and the poikilothermic invertebrate vector. The ability to resist temperature and other stresses is essential for trypanosome survival. Trypanosome gene expression is mainly post-transcriptional, but must nevertheless be adjusted in response to environmental cues, including host-specific physical and chemical stresses. We investigate here the control of ZC3H11, a CCCH zinc finger protein which stabilizes stress response mRNAs. ZC3H11 protein levels increase at least 10-fold when trypanosomes are stressed by heat shock, proteasome inhibitors, ethanol, arsenite, and low doses of puromycin, but not by various other stresses. We found that increases in protein stability and translation efficiency both contribute to ZC3H11 accumulation. ZC3H11 is an in vitro substrate for casein kinase 1 isoform 2 (CK1.2), and results from CK1.2 depletion and other experiments suggest that phosphorylation of ZC3H11 can promote its instability in vivo. Results from sucrose density centrifugation indicate that under normal culture conditions translation initiation on the ZC3H11 mRNA is repressed, but after suitable stresses the ZC3H11 mRNA moves to heavy polysomes. The ZC3H11 3'-UTR is sufficient for translation suppression and a region of 71 nucleotides is required for the regulation. Since the control works in both bloodstream forms, where ZC3H11 translation is repressed at 37°C, and in procyclic forms, where ZC3H11 translation is activated at 37°C, we predict that this regulatory RNA sequence is targeted by repressive trans acting factor that is released upon stress.
Gesehen am 19.05.2020